PENGARUH RELIGIUSITAS DAN KEGIATAN SPIRITUAL TERHADAP PERSEPSI TINGKAT KEAMANAN DI INDONESIA - Abdullah, Zaki; Jubba, Hasse (IAIN Palangka Raya, 2020)
Both religiosity and spiritual activities could improve security perceptions by reducing crime rates in Indonesia. However,